Religious politics and secular states: Egypt, India, and the United States - Hibbard, Scott W. (Johns Hopkins Univ. Press, 2010)
Reinterpreting modern religious politics -- The rise and decline of Egyptian secularism -- The rise and decline of Egyptian politics -- The rise and decline of Indian secularism -- Embedding communalism in Indian politics -- The rise and decline of American secularism -- Religious nationalism in the Reagan-Bush era